A comprehensive review of response control systems for irregular buildings: exploring base isolators and dampers - Pramod Kumar; Abhilash Gogineni; Subrat Kumar Sahu; Animesh Kumar Singh; Bamidele Charles Olaiya (Discover Applied Sciences)
Abstract Ensuring structural regularity during construction presents significant challenges but is essential for mitigating vulnerabilities to dynamic forces such as wind and seismic loads. Structural irregularities amplify a building’s susceptibility to these forces, necessitating the implementation of advanced response control systems. Base isolation and damping technologies serve as effective mitigation strategies by reducing structural response to external excitations. While response control is not a novel concept, ongoing research has reviewed the development of modified and hybrid control systems that enhance performance. A comprehensive review of response control applications in irregular buildings demonstrates their substantial effectiveness, with reductions in structural response exceeding 50% compared to uncontrolled structures. Base isolation employs flexible bearings to decouple a structure from ground motion, while damping systems dissipate vibrational energy, reducing structural deformations and stresses. These technologies are essential for safeguarding structures in seismically active regions and areas subjected to extreme wind loads. Ongoing research in response control methodologies continues to yield improvements, further enhancing structural performance and safety. The evolution of these systems underscores the importance of proactive engineering strategies in mitigating seismic risks, ensuring structural integrity, and protecting lives and property against the devastating effects of earthquakes and other dynamic forces.